Peripheral Arterial Disease Study (PERART): Prevalence and predictive values of asymptomatic peripheral arterial occlusive disease related to cardiovascular morbidity and mortality - Bundó Magda; Llussà Judith; Albaladejo Carlos; Reina María; Pera Guillem; Vicheto Marisa; Toran Pere; Forés Rosa; Sorribes Marta; Baena-Díez José; Alzamora María; Sancho Amparo; et al. (BMC, 2007)
Abstract Background The early diagnosis of atherosclerotic disease is essential for developing preventive strategies in populations at high risk and acting when the disease is still asymptomatic. A low ankle-arm index (AAI) is a good marker of vascular events and may be diminished without presenting symptomatology (silent peripheral arterial disease). The aim of the PERART study (PERipheral ARTerial disease) is to determine the prevalence of peripheral arterial disease (both silent and symptomatic) in a general population of both sexes and determine its predictive value related to morbimortality (cohort study). Methods/Design This cross-over, cohort study consists of 2 phases: firstly a descriptive, transversal cross-over study to determine the prevalence of peripheral arterial disease, and secondly, a cohort study to evaluate the predictive value of AAI in relation to cardiovascular morbimortality. From September 2006 to June 2007, a total of 3,010 patients over the age of 50 years will be randomly selected from a population adscribed to 24 healthcare centres in the province of Barcelona (Spain). The diagnostic criteria of peripheral arterial disease will be considered as an AAI < 0.90, determined by portable Doppler (8 Mhz probe) measured twice by trained personnel. Cardiovascular risk will be calculated with the Framingham-Wilson tables, with Framingham calibrated by the REGICOR and SCORE groups. The subjects included will be evaluted every 6 months by telephone interview and the clnical history and death registries will be reviewed. The appearance of the following cardiovascular events will be considered as variables of response: transitory ischaemic accident, ictus, angina, myocardial infartction, symptomatic abdominal aneurysm and vascular mortality. Discussion In this study we hope to determine the prevalence of peripheral arterial disease, especially the silent forms, in the general population and establish its relationship with cardiovascular morbimortality. A low AAI may be a better marker of arterial disease than the classical cardiovascular risk factors and may, therefore, contribute to improving the predictive value of the equations of cardiovascular risk and thereby allowing optimisation of multifactorial treatment of atherosclerotic disease.